Sound and signals - Tohyama, Mikio 1947- (Signals and communication technology, 2011)
This is an up-to-date reference and textbook on modern acoustics from a signal-theoretic point of view, as well as a wave-theoretic approach for students, engineers, and researchers. It provides readers the fundamental basis of acoustics and vibration science and proceeds up to recent hot topics related to acoustic transfer functions and signal analysis including a perceptual point of view. In the first part, the work uniquely introduces into the fundamentals without using heavy mathematics The following, advanced chapters deal with new and deep insights into acoustic signal analysis and investigation of room transfer functions based on the poles and zeros.